PCR for Screening of Multidrug Resistant Acinetobacter baumannii by MexA, MexB Like Gene and 16-23S rRNA Intergenic Spacer Region (ISR) - Kongcharoensuntorn, Wisatre; Teyasingh, Rada (Burapha Science Journal, 2026)
This research was aimed to identify MexA and MexB like gene in Acinetobacter baumannii from clinical isolates and compare it among some opportunistic bacteria. The MexA and MexB gene was analyzed and compared by PCR and confirmed the difference of A. baumannii among other species by 16S - 23S rRNA Intergenic Spacer Region (ISR). The results of research could amplify both the MexA and MexB like DNAs from multidrug-resistant A. baumannii of which was not found in nondrug-resistant A. baumannii among all clinical isolates from Rayong Hospitals and Chonburi Hospital, collected during March to December 2016. Thus, the research was revealed that these Mex A and MexB like genes dispread in the two provinces, and these genes contained PCR products of 1,175 and 2,300 base pairs, respectively. Also, identification of A. baumannii by using ISR primer could indicate that twenty isolates of both multidrug-resistant A. baumannii and non multidrug-resistant A. baumannii contained 1,258 base pairs of ISR. Thus, PCR could be applied to select out multidrug-resistant A. baumannii and discrete from other opportunistic bacteria. This method also included to study evolution of resistant bacteria and incidence of outbreaks for treatment and prevention of A. baumannii infection in the future.